B Chromosomes in Psalidodon scabripinnis (Characiformes, Characidae) Species Complex - Silva, Duilio M. Z. A. [UNESP] (2022)
Simple Summary For more than a century, B chromosomes have been investigated in several eukaryotic species. These supernumerary genomic elements behave as parasites or provide fitness benefits to the hosts. They are mostly composed of repetitive DNA, but they also have protein-coding genes. B chromosomes are associated with differential gene expression and phenotypic effects. This makes them one of the most interesting genomic elements to investigate. Fish species of the Psalidodon genus harbor a great diversity of B chromosomes. Recent studies showed they share a common ancestor, persisting in the genus for a long time and enduring speciation processes. In the Psalidodon scabripinnis species complex, B chromosomes express their own genes, mostly related to cell cycle and gonad differentiation. Moreover, these B chromosomes are associated with functional effects, e.g., cell cycle extension. Here, we review the current knowledge regarding these elements in the P. scabripinnis species complex and propose a chromosome speciation model facilitated by the B chromosome manipulation of the cell machinery. B chromosomes are extra-genomic components of cells found in individuals and in populations of some eukaryotic organisms. They have been described since the first observations of chromosomes, but several aspects of their biology remain enigmatic. Despite being present in hundreds of fungi, plants, and animal species, only a small number of B chromosomes have been investigated through high-throughput analyses, revealing the remarkable mechanisms employed by these elements to ensure their maintenance. Populations of the Psalidodon scabripinnis species complex exhibit great B chromosome diversity, making them a useful material for various analyses. In recent years, important aspects of their biology have been revealed. Here, we review these studies presenting a comprehensive view of the B chromosomes in the P. scabripinnis complex and a new hypothesis regarding the role of the B chromosome in the speciation process.